Addressing Water Scarcity in Isla Huichas, Chile: A Tecno-Economic Sustainable Solution - Benjamín Borquez; José Ahumada; Michael Mendoza; Renny Guillén; Victor Contreras (World, 2024)
Islas Huichas, located in Chile’s remote Aysén region, has long faced water scarcity due to a lack of natural sources. The community relies on rainwater collection pools managed by the Rural Drinking Water Committee (RDWC), which face increased pressure during the summer tourist season, leading to frequent shortages. In 2014, a Reverse Osmosis (RO) plant with a 240 m3 daily capacity was installed to address the issue. While the RO plant helps alleviate summer shortages, it has high energy costs and maintenance challenges, exceeding the financial capacity of the RDWC. This study evaluates various scenarios to reduce the plant’s operational costs and emissions reduction.